Ocular manifestations in HIV patients and its correlation with CD4 count before and after starting HAART - Shraddha More; Prashant More; Dhiraj Badale (Asian Journal of Medical Sciences, 2022)
Background: Human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS) are a global pandemic, with cases reported from practically every country. The majority of information and studies regarding ophthalmic manifestations in India reflects the pre-HAART (highly active anti-retroviral therapy) era. India may be going through an intermediate stage, where the spectrum of the ophthalmological manifestations may be changing significantly. Aims and Objectives: The aims of this study were to study the age and gender distribution in HIV patients presenting with various ocular manifestation and to correlate the cluster of differentiation 4 (CD4) count with various ocular manifestation of AIDS. Materials and Methods: Prospective cross-sectional study was conducted on 120 patients. Ocular manifestations and WHO clinical stage of HIV were noted and CD4 count was calculated. The participants were followed up for at least 6 months on monthly basis when they come to take ART tables or as required for any ophthalmic disorder presented by patient. Any manifestation during this months was included in post HAART group. CD4 count after 6 months was taken into account in post HAART group. Results: Males predominated females. The number of males in Pre HAART was 60.8% and post-HAART 59.4%. Mean CD4 count in pre-HAART was 140.63 and post-HAART was 221.93. Majority (34 patients) in pre-HAART had CD4 count between 100 and 150, while in post-HAART, majority had count more than 200 (57 patients). Conclusion: Mean CD4 count of pre-HAART group patients raised significantly. Mean CD4 count of pre-HAART group is 140.63 with SD of 63.4, while it increased in post-HAART group to 222 which is statistically highly significant.